Desain Kota Karton Gelombang Sebagai Kemasan Keramik Guci Untuk Ekspor - Zoherly Zoherly (Balai Besar Kimia dan Kemasan, 1999)
Several design of corrugated carton boxes for ceramics vase have been developed by using single and double wall corrugated carton with different gramature 1251125/125,15011501150 and 150112511251150. The evaluation is made by comparing their characteristic through the physical test such as compression, drop and vibration test. The result shows that the single wall corrugated board with gramature 15011501150 have good physical characteristic. With regard to the economic point of view, the gramatur15011501150 single wall corrugated board is recommended for packaging of cearamics vase, especially for export.